Justice - Campbell, Tom. (New York, 2010)
Justice is one of those core moral and political terms which claim universal importance and feature centrally in all social and political theories. Indeed, for many theorists it is the prime and overarching concept of public life, although it is increasingly overshadowed by the global attention being accorded to human rights, a phenomenon which is discussed in Chapter 12. The almost universal popularity of justice breeds a diversity of analyses and applications of the term 'justice' which can bewilder and discourage those who seek precision and clarity in their approach to political issues. Disagreement abounds over what it means to call a situation just or unjust, about what sort of actions are just or unjust, about who ought to do what to bring about justice, and about how we should go about settling these controversial matters. This book seeks to provide an overview of this contentious territory, explor ing and testing those claims to universal value which the language of justice evokes, outlining a framework within which to compare and assess theories of justice, and suggesting how we might arrive at our own views on what justice is about and what sort of principles of justice we ought to adopt.
Keywords: Justice-Theory